2016
DOI: 10.1111/neup.12284
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and organ‐related marker expression in pituitary adenomas

Abstract: The histologic expression of epithelial and organ-related immunohistochemical markers in primary sellar region tumors has received little attention to date. This lack of empirical data may lead to mistaken assumptions in the evaluation of sellar region neoplasms. To address this issue, the frequency and specificity of epithelial (cytokeratin 7(CK7), CK20) and organ-related differentiation markers (gross cystic disease fluid protein-15 (GCDFP-15), thyroid transcription factor-1 (TTF-1), Napsin A, paired box 8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, some authors implied a participation of neural crest-derived cells ( 9 , 11 ). The immunohistochemical results of positivity for CAM5.2 and CK7 but negativity for CK20 were confirmed in a subpopulation of NENs as well as that of pituitary adenomas, which may indicate organ-related differentiation in neoplasms ( 38 , 74 ). While the European Pituitary Pathology Group has proposed the diagnostic algorithms for PitNETs, it is interesting to note that the pathological features of GCs/MGAs are more similar to those of NENs than to those of functional adenomas ( 67 , 75 ).…”
Section: Discussionmentioning
confidence: 69%
“…However, some authors implied a participation of neural crest-derived cells ( 9 , 11 ). The immunohistochemical results of positivity for CAM5.2 and CK7 but negativity for CK20 were confirmed in a subpopulation of NENs as well as that of pituitary adenomas, which may indicate organ-related differentiation in neoplasms ( 38 , 74 ). While the European Pituitary Pathology Group has proposed the diagnostic algorithms for PitNETs, it is interesting to note that the pathological features of GCs/MGAs are more similar to those of NENs than to those of functional adenomas ( 67 , 75 ).…”
Section: Discussionmentioning
confidence: 69%
“…It is also expressed in the ventral forebrain and pituitary in rodents and in normal human pituicytes which originate from the ventral ectoderm ( 74 ). In a prior study, TTF-1 was found to be positively expressed in all subtypes of PPTs and was negative in normal or tumoral adenohypophyseal tissue ( 75 ). A recent study has reported a new entity PPETS, also expressing TTF-1 ( 15 ).…”
Section: Discussionmentioning
confidence: 89%
“…These cells contain cytoplasmic extensions resembling folliculostellate cells found in the anterior pituitary may look like a metastatic lesion. Therefore, the distribution pattern of CK7 positive cells is important since a diffuse pattern will most likely favor a metastatic neoplasm (13). No adenomas were ever found to have diffuse, strong CK7 immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%